Local Ecological Knowledge and Fishing Practices of Fishermen on Barrang Lompo Island, Makassar City - Idrus, Idham Irwansyah; Ismail, Ashari; Mappe, Ulfa Utami; Salwia, Salwia (Society, 2025)
Marine ecosystems in small coastal and island communities play a vital role in sustaining local livelihoods. This study adopts a phenomenological approach, following the Stevick-Colaizzi-Keen method, to examine the forms of local ecological knowledge (LEK) held by fishermen on Barrang Lompo Island and how this knowledge informs their fishing practices. Drawing on Coleman’s Rational Choice Theory, the findings demonstrate that fishing behavior is shaped by ecological knowledge acquired through prolonged environmental interaction and passed down through generations. Rituals, traditions, and the use of ecologically responsive fishing gear are not merely cultural expressions; they are part of rational decision-making shaped by factors such as financial resources, anticipated returns, type of catch, availability of labor and equipment, market demand, pricing, and risk assessment. The choice to use or refrain from using fish bombs, for instance, reflects deliberate reasoning grounded in both experience and ecological insight. This study offers a sociological perspective on fishermen’s motivations and knowledge systems, contributing to the broader conservation discourse and highlighting the importance of knowledge transmission for fostering sustainability within fishing communities.